ANALISIS SPASIAL TINGKAT BAHAYA GEMPABUMI BERDASARKAN KARAKTERISTIK DINAMIKA TANAH KOTA PADANG, SUMATERA BARAT - , Saaduddin ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study processed 103 points of mictremor measurement data of Padang that observed by Pusat Survey Geologi, Badan Geologi, Kementrian Energi dan Sumber Daya Mineral on November 26th-30th, 2009. The objective of this study is to know the dynamics characterics of soil which is used as the parameters to map the seismic hazard area in Padang, based on data of microtremor and seismicity. The parameters are dominant frequency ðð, amplification ð´ð, dominant period ðð, seismic vulnerability index ð¾ð, thickness of sediment layer ð, peak ground acceleration on surface ðð , peak ground acceleration on bed rock ðð, ground shear strain ð¾, and b-value. The result showed that the dominant frequency ðð is about (0.42 â 12.12) Hz,, the amplification ð´ð is about (1.54 â 10.67), the dominant period ðð is about (0.08 â 2.36) s, the seismic vulnerability index ð¾ð is about (0.58 â 170.61), the thickness of sediment layer ð is about (6.78 â 270.07) m, the peak ground acceleration on surface ðð is about (101.25 â 463.875) gal, the peak ground acceleration on bed rock ðð is about (76.51 â 85.76) gal, the ground shear strain ð¾ is about (4.85 x 10-5 â 1.45 x 10-2) and the b-value is about (0.90 â 1.40). Based on those parameters, the classification of seismic hazard area in Padang showed that the western part of Padang is in medium to high seismic hazard. The low seismic hazard is in the eastern of Padang such as Pauh, part of Lubuk Bergalung, part of Lubuk Kilangan and apart of Kuranji. The high seismic hazard is almost in coast area like Padang Utara, northern of Padang Timur, northern of Padang Barat and part of Naggalo and Kuranji